PRINSIP-PRINSIP KESOPANAN DALAM FILM ANIMASI â€œMOANAâ€ KARYA JOHN GRIERSON (Suatu Kajian Pragmatik) - SAUBANI, SUSI SUSANTI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
ABSTRACT This research entitled â€œPrinsip-Prinsip Kesopanan dalam Film Animasi â€œMOANAâ€ Karya John Grierson: Suatu Analisis Pragmatikâ€ focuses on maxim related to the principle of politeness. The problems of this research are: What kinds of Politeness Principles used by the character in â€œMoanaâ€ & What are the functions of Politeness Principles used by the main character in â€œMoanaâ€ movie.Â The purpose of this research is to identify, classify, analyze the function and types of politeness in maxim used that can be shown in the conversation in the animation movie. In collecting data, the writer concentrates the utteranceâ€Ÿs which contains the principles of politeness produced by the main character in the movie. The collected data are analyzed based on Leechâ€Ÿs theory.Â The results shows that there are six types of maxim from the utterances of the main character in the animation movie â€œMOANAâ€ they are: tact maxim, generosity maxim, approbation maxim, modesty maxim, agreement maxim and sympathy maxim. It is expected that this research will help the students and other readers in learning the pragmatic aspects, especially about maxim in politeness principles. Â Keyword: Politeness Principles, Pragmatic, Movie: Moana